The Influence of Job Stress, Organizational Culture, and Organizational Communication on Turnover Intention in X Hospital - Cindy Clarista Saputan, Hasyim, Rokiah Kusumapradja (Jurnal Cinta Nusantara, 2023)
The high rate of Turnover is a negative thing and is detrimental to the Hospital. This problem can have an impact on material losses, effectiveness and human resources. The purpose of this study was to analyze the effect of job stress, organizational culture and organizational communication on turnover intention at RS X. This research method is a quantitative research to look at the factors that are related to the desire of employees to stop working with a survey research design. The analysis technique used is Multiple Linear Regression. The sample population of this study were all nurses in X Hospital in total of 157 respondents. The sampling technique uses a saturated sample. Measurements in this study used questionnaires that were distributed to 157 respondents and questionnaires that returned a total of 157 sets of questionnaires. The results of the study show that job stress, organizational culture and organizational communication have an influence on turnover intention in RS X. Job stress has no effect on turnover intention. Organizational culture influences turnover intention, and organizational communication influences turnover intention. The implications of research for management so that employee turnover intention is reduced by re-evaluating workload calculations, creating a remuneration system and improving work shift regulations to reduce job stress, besides that management is expected to provide clear information directions on every detail of work and provide prizes to employees who excel to increase.